Comparative Diversity of Gastropods and Bivalves Among Coastal Habitats - Dwi Sri Wahyuni; Dana Kaye Donato; Choirunnisa Adinda Mulyana; M Haikal Almahdi; Alifia Siti Nurjanah; Annisa Nurhasanah; Meilisha Putri Pertiwi (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2026)
Gastropods and bivalves are important components of coastal ecosystems, functioning as detritivores, grazers, and filter feeders, as well as serving as bioindicators of environmental conditions. However, recent data on mollusc biodiversity in Pari Island remain limited, despite increasing anthropogenic pressures such as tourism and coastal pollution. This study aimed to assess the diversity and community structure of gastropods and bivalves across three coastal ecosystems on Pari Island, Seribu Islands, Jakarta, namely Star Beach, Virgin Sand Beach, and mangrove areas. Sampling was conducted using a combination of direct sampling and time searching methods, with four researchers collecting specimens for 30 minutes at each site, while abiotic parameters (temperature, pH, salinity, and humidity) were measured simultaneously. The results showed that Star Beach exhibited the highest diversity, with low dominance and high evenness, indicating a stable and balanced ecosystem supported by heterogeneous sandy substrates. The mangrove ecosystem showed moderate diversity with relatively even species distribution, reflecting its role as a habitat for specialized gastropods adapted to muddy, organic rich conditions. In contrast, Virgin Sand Beach had low diversity and low evenness, with strong dominance of the Neritidae family, particularly Clithon oualaniense, indicating ecological pressure and reduced environmental stability likely caused by intensive tourism activities. These differences in community structure are strongly influenced by habitat characteristics and abiotic factors, where substrate type, salinity, and humidity play key roles in shaping species distribution. This study highlights that habitat type and environmental conditions are major drives of mollusc diversity, while also emphasizing the negative impact of anthropogenic disturbance on ecosystem balance. The findings provide updated baseline data on mollusc diversity in Pari Island and contribute to supporting sustainable coastal management and marine biodiversity conservation in small island ecosystems such as the Seribu Islands.